Simulation Games in Teaching International Relations: Insights from a Multi‐Day, Multi‐Stage, Multi‐Issue Simulation on Cyprus. Issue 4 (5th April 2013) - Hatipoglu, Emre; Müftüler‐Baç, Meltem; Murphy, Teri
<x xml:space="preserve">Abstract</x> This article reviews experiences from a large‐scale student simulation, which concluded the Istanbul Conference on Mediation: Enhancing Peace through Mediation that took place in February 2012. We share insights on two unique aspects of the simulation. First, the paper examines a rare case where the simulation crossed paths with real life: a number of the impersonated officials (and offices) including the president of the General Assembly of the UN, the Minister of Foreign Affairs of Turkey, and the Director of the Policy and Mediation Division of the UN Department of Political Affairs were in the audience and shared their impressions. Second, the setup of the simulation was more complex than its typical in‐class counterparts. Our insights from this multi‐day, multi‐stage, and multi‐issue simulation can inform colleagues who plan to run larger scale simulations. Besides sharing experiences on a number of logistical points, we especially draw attention to the constructive role facilitators can play in augmenting the learning benefits accruing to the students from simulations.